2011
DOI: 10.3917/gs.138.0217
|View full text |Cite
|
Sign up to set email alerts
|

Vieillesses ordinaires en solitude

Abstract: Distribution électronique Cairn.info pour Fondation Nationale de Gérontologie. © Fondation Nationale de Gérontologie. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…(Odette, 79 years old, widow with children, 27 years of solo living)The accounts given by the seniors we met revealed that they sometimes experienced several forms of loneliness, although not necessarily contingent on specific times. These first observations are consistent with Campéon's findings regarding French seniors, which showed that ‘the feeling of loneliness occurs in phases, namely that it can be “activated” or more severely feared at particular times of the day or in certain places’ (Campéon, 2011: 221, free translation). Conversely, only a few of the seniors we met reported experiencing ‘static’ loneliness.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…(Odette, 79 years old, widow with children, 27 years of solo living)The accounts given by the seniors we met revealed that they sometimes experienced several forms of loneliness, although not necessarily contingent on specific times. These first observations are consistent with Campéon's findings regarding French seniors, which showed that ‘the feeling of loneliness occurs in phases, namely that it can be “activated” or more severely feared at particular times of the day or in certain places’ (Campéon, 2011: 221, free translation). Conversely, only a few of the seniors we met reported experiencing ‘static’ loneliness.…”
Section: Resultssupporting
confidence: 87%
“…This literature states in particular that, for a senior, the facts of living alone (De Jong Gierveld et al ., 2011; Wenger and Burholt, 2004; Havens et al ., 2004), being very old (Jylhä, 2004; Wenger and Burholt, 2004; Penning et al ., 2014), being a woman 4 (Aartsen and Jylhä, 2011; Beaumont, 2013), having physical or mental health problems or perceiving oneself as such (Grenade and Boldy, 2008; Beaumont, 2013; De Jong Gierveld et al ., 2015), being single (De Jong Gierveld et al ., 2011; Beaumont, 2013), having an unsatisfactory social network (Victor et al ., 2000; Pinquart, 2003) as well as being socio-economically disadvantaged or ‘perceiving oneself as poor’ (Ajrouch et al ., 2005; De Jong Gierveld et al ., 2015) expose individuals to the risk of experiencing loneliness. In addition, a much smaller body of research has examined seniors’ experiences of loneliness through qualitative research methods (McInnis and White, 2001; Hall et al ., 2003; Sand and Strang, 2006; Dahlberg, 2007; Pettigrew and Roberts, 2008; Hauge and Kirkevold, 2010; Campéon, 2011; Sullivan et al ., 2016). In this regard, some authors stress the need for future studies to provide more qualitative analyses that can shed light on the meaning that seniors give to ‘their’ loneliness, as well as on their social conditions, which are commonly referred to as their main risk factors (Victor et al ., 2000; British Columbia Ministry of Health, 2004; Hauge and Kirkevold, 2010; Sullivan et al ., 2016).…”
Section: Loneliness Among Seniorsmentioning
confidence: 99%
“…Clément et al [5] studied the neighbourly relations of the elderly as a mean of overcoming some of the loneliness. In "La solitude du chez soi : Un territoire sans partage ", Campéon [6] discusses the link between loneliness and the type of housing.…”
Section: Senior Citizens' Housingmentioning
confidence: 99%
“…In accordance with the Aging Population and Habitat Workshop 6 , we have studied the « needs in terms of new technologies for residents in a shared home, in a rural area » within a True Live Lab (TTL) [3], a method of deployment of innovations which were codesigned in an « ecological » environment. The expression of the technology needs was first collected on-site, in the shared house of Montredon.…”
Section: Introductionmentioning
confidence: 99%
“…2009 ;Soullier et Weber, 2011), l'étude de l'aide et de l'entraide au sein des couples âgés (Renaut et collab. 2018) ou encore celle de la solitude et de l'isolement (De Jong Gierveld, 1998 ;Litwin, 2010 ;Campéon, 2011). Dans cet article, nous ne nous intéresserons pas à l'aide portée à un aîné en situation de perte d'autonomie, mais aux autres formes de soutien, non directement liées à l'état de santé.…”
Section: Introductionunclassified